نهر الخوصر في نينوى في ضوء تقانة التحسس النائي - الكروي، رؤى زهير زيدان (جامعة بغداد - مركز إحياء التراث العلمي العربي, 2016)
The river "Al Khawser" has a significant role in the history of civilization of Nineveh city in north of Iraq that makes studying river channel and previous geomorphological analysis with its relation to the political and economical in the city in the ancient history depending on remote sensing technology with aerial imagery interpretation because it is easily available, multiple use, engineered integration, and low cost compared to other technology, this paper discovered that the current channel of river "Al Khawaser" is not the real old path. This paper studied and discovered that the current location of outer moat besides the current soil wall is the real river channel of Al-Khawser which was flow in Tigris River at Yaaremjah location now. This occurred before building of Nineveh city which became part of its outer design. The paper's results were enhanced by a number of field pictures of Nineveh city location in addition to number of images taken through Google Earth to support the basic maps of the ancient city.
إن لنهر الخوصر دور أساسي في التاريخ الحضاري لمدينة نينوى الأثرية فأن البحث حول مجرى هذا النهر وتحليل الوضع الجيومورفولوجي السابق له وعلاقته مع الوضع السياسي والاقتصادي السابق للمدينة الأثرية، بالاعتماد على تقنية التحسس النائي وتفسير الصور الجوية، لسهولة توفرها ولتكاملها الهندسي واستعمالاتها المتعددة وتكلفتها القليلة مقارنة مع التقنيات الأخرى، سهل الوصول إلى أن مجرى نهر الخوصر الحالي داخل مدينة نينوى الأثرية هو ليس المجرى الأصلي. كما توصل البحث إلى أن موقع الخندق الخارجي المجاور للسور الترابي هو المجرى الأصلي والذي كان يصب في نهر دجلة عند موقع يارمجة الحالي، وهذا قبل بناء مدينة نينوى وقبل أن يصبح جزءا من خطة تصميم شكلها الخارجي. عززت النتائج بعدد من الصور الحقلية لموقع مدينة نينوى، فضلا عن عدد من المرئيات الملتقطة من برنامج Google Earth لدعم ما أنجزناه من خرائط أساسية توضيحية لموقع المدينة الأثرية.
Keywords: نهر الخوصر -- تقانة التحسس النائي -- نينوى -- العراق